Rethinking system boundaries of the life cycle carbon emissions of buildings. (July 2018) - Pan, Wei; Li, Kaijian; Teng, Yue
Abstract: There is a strong consensus that carbon emissions attributed to buildings are a major contributor to global warming. Reducing buildings' carbon emissions becomes a matter of urgency and importance. However, despite the burgeoning body of knowledge of addressing buildings' carbon emissions in the life cycle assessment (LCA) approach, the system boundaries of buildings' carbon emissions and actually of their relevant research had never been made explicit systemically. As a result, the definitions of buildings' life cycle differ considerably and the methods and models of analyzing buildings' life cycle carbon emissions (LCCa) vary; all these lead to discrepancies in reported buildings' LCCa and suggest a significant knowledge gap in effectively addressing the complex socio-technical features of buildings' LCCa. This paper aims to provide a fundamental rethink of the boundaries of buildings' LCCa for achieving meaningful benchmarking and learning in the future. The paper proposes a conceptual framework of system boundaries of buildings' LCCa, and develops a regression model to predict such LCCa with strategies for enhancing the validity and reliability of the prediction. The framework elaborates the boundaries of buildings' LCCa in the temporal, spatial, functional and methodological dimensions which together contain twelve variables, namely, life cycle stage, lifespan, climatic zone, geographic scope, LCA method, research method, unit of analysis, sources of emissions, building typology, level of prefabrication, building material, and density. The regression model is validated utilizing six representative cases of buildings' LCCa selected globally. Inconsistent system boundaries adopted were found to have contributed to the discrepancies between the resultant buildings' LCCa. The reconstructed system boundaries and developed regression model should facilitate a paradigmatic improvement in the body of knowledge of buildings' LCCa. Highlights: Framework of system boundaries of buildings' lifecycle carbon (LCCa) is established. The boundaries are in temporal, spatial, functional and methodological dimensions. A regression model is developed to predict LCCa with validity and reliability. The model is validated utilizing six representative cases of buildings' LCCa. Inconsistent boundaries were found to contribute to LCCa discrepancies of the cases.